PEREMPUAN PEKERJA DALAM HUBUNGAN PATRON KLIEN; KASUS PENGRAJIN SAPU IJUK DI DESA BARIKIN - Ahmad Muzakkir (Universitas Islam Negeri Imam Bonjol Padang, 2012)
The relationship between patron with clients can be seen from the reciprocal relationship between the collector with the craftsmen and vice versa. Relationships in business activities in the form of craftsmen as the client provides energy for business patron or collector to make broomstick fibers, while the collector provide jobs and wages to the results of the work done by the craftsmen. Outside activities such as collecting lend assistance to artisans who are in need. On the other hand craftsmen donated labor either at the collector requires artisans to organize an event or gathering babysitting without being rewarded. Copyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i2.61